Physical and chemical characteristics of Asian sea bass bio‐calcium powders as affected by ultrasonication treatment and drying method. Issue 4 (17th February 2021) - Wijayanti, Ima; Sookchoo, Pornsatit; Prodpran, Thummanoon; Mohan, Chitradurga O.; Aluko, Rotimi E.; Benjakul, Soottawat
Abstract: The effects of ultrasonication and drying method on particle size and other product characteristics of bio‐calcium powder from Asian sea bass ( Lates calcarifer ) backbone were investigated. Ultrasonication was performed at different amplitudes (60%, 70%, and 80%) for varying periods (15 and 30 min). Ultrasonication at higher amplitudes for a longer time reduced the powder particle size more effectively ( p < .05), but had no impact on zeta potential ( p > .05). The bio‐calcium powder ultrasonicated at 70% amplitude for 15 min had the smallest particle size (3.38 µm) when compared to the control (28.85 µm). When the ultrasonicated bio‐calcium was subjected to drying, freeze‐drying produced powders with higher calcium solubility but lower whiteness than hot air (tray) drying. The results suggest that the ultrasonication is a potential suitable method to reduce the size of bio‐calcium powders, while the drying method slightly affected the product characteristics. The bio‐calcium powder could serve as a suitable functional ingredient for food fortification aimed at improving the calcium bioavailability. Particle size of bio‐calcium powder from fishbone could affect the mouth feel and calcium solubility when used for food product fortification. This work showed that ultrasonication could be used to obtain up to 10‐fold reduction in the particle size of fishbone bio‐calcium powders, which promotes increased calcium solubility when subjected to simulated gastrointestinal tract digestion. Few differences in characteristics of the bio‐calcium powder were observed for freeze‐dried and hot air‐dried samples. Thus, an economical, safe, and fast process can be implemented for the production of small particle size bio‐calcium powder from fishbone. Abstract : Reduced particle size was achieved with the aid of ultrasonication Drying had no effect on color of bio‐calcium Better solubility was attained for freeze‐dried bio‐calcium